Minutes of 7th technical and progress monitoring (TPM) meeting of BRACU new campus (session Il) - Brac University (Brac University, 2023)
Minutes of the 7th Technical and Progress Monitoring (TPM) meeting (session Il) of BRACU new campus, held on 20th December, 2018.